2010
DOI: 10.1021/jm100076w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Potent and Selective Amidobipyridyl Inhibitors of Protein Kinase D

Abstract: The synthesis and biological evaluation of potent and selective PKD inhibitors are described herein. The compounds described in the present study selectively inhibit PKD among other putative HDAC kinases. The PKD inhibitors of the present study blunt phosphorylation and subsequent nuclear export of HDAC4/5 in response to diverse agonists. These compounds further establish the central role of PKD as an HDAC4/5 kinase and enhance the current understanding of cardiac myocyte signal transduction. The in vivo effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…Furthermore, phosphorylation of these residues, which flank a nuclear localization signal domain in both HDAC4 and HDAC5, has been causally implicated in the neurohormonal induction of HDAC nuclear export and thereby the disinhibition of MEF2-driven transcriptional reprogramming that facilitates myocyte hypertrophy. 4,26 We therefore explored the individual regulation of HDAC4 and HDAC5 in ARVM through heterologous expression of their FLAG epitope-tagged variants (FLAG-HDAC4 and FLAG-HDAC5), using a newly described selective PKD inhibitor (identified as compound 12a 27 or bipyridyl PKD inhibitor [BPKDi] 28 ) to confirm the role of PKD activity in their ET1-induced phosphorylation. In an initial step, we extended the recent pharmacological characterization of BPKDi 27,28 by screening it against a larger panel of Ͼ120 protein kinases using validated in vitro kinase assays, 21 which underscored the inhibitor's remarkable selectivity for PKD (Online Table I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, phosphorylation of these residues, which flank a nuclear localization signal domain in both HDAC4 and HDAC5, has been causally implicated in the neurohormonal induction of HDAC nuclear export and thereby the disinhibition of MEF2-driven transcriptional reprogramming that facilitates myocyte hypertrophy. 4,26 We therefore explored the individual regulation of HDAC4 and HDAC5 in ARVM through heterologous expression of their FLAG epitope-tagged variants (FLAG-HDAC4 and FLAG-HDAC5), using a newly described selective PKD inhibitor (identified as compound 12a 27 or bipyridyl PKD inhibitor [BPKDi] 28 ) to confirm the role of PKD activity in their ET1-induced phosphorylation. In an initial step, we extended the recent pharmacological characterization of BPKDi 27,28 by screening it against a larger panel of Ͼ120 protein kinases using validated in vitro kinase assays, 21 which underscored the inhibitor's remarkable selectivity for PKD (Online Table I).…”
Section: Resultsmentioning
confidence: 99%
“…4,26 We therefore explored the individual regulation of HDAC4 and HDAC5 in ARVM through heterologous expression of their FLAG epitope-tagged variants (FLAG-HDAC4 and FLAG-HDAC5), using a newly described selective PKD inhibitor (identified as compound 12a 27 or bipyridyl PKD inhibitor [BPKDi] 28 ) to confirm the role of PKD activity in their ET1-induced phosphorylation. In an initial step, we extended the recent pharmacological characterization of BPKDi 27,28 by screening it against a larger panel of Ͼ120 protein kinases using validated in vitro kinase assays, 21 which underscored the inhibitor's remarkable selectivity for PKD (Online Table I). We also confirmed the ability of BPKDi to inhibit PKD activity in ARVM at concentrations Ͼ1 mol/L (Online Figure I), with the lower potency reflecting the higher ATP concentration in cells relative to that used for in vitro kinase assays, as observed also for other ATP-competitive kinase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibitors targeting PKD1 such as BPDKi have been developed but this aminobipyridyl compound failed to blunt animal cardiac hypertrophy (31). Our new results call for further tests on PKD3-selective inhibitors or pan-PKD inhibitors to determine their efficacy in blunting cardiac hypertrophy and heart failure.…”
Section: Discussionmentioning
confidence: 97%
“…Mice with PKD1 ablation show substantial resistance to cardiac hypertrophy (30). Unexpectedly, a recent study reported a newly developed PKD1-selective inhibitor failed to attenuate PCH in whole animal models (31). One possible explanation for such a discrepancy is that PKD3 could substitute for PKD1 as a HDAC5 kinase as documented in non-cardiac cells (32).…”
Section: Pathological Cardiac Hypertrophy (Pch)mentioning
confidence: 99%
“…HDAC subtype-specific inhibition might be a way to resolve this benefit conflict, but targeting upstream of HDACs may hold unique benefits. Along these lines, cardiac-specific deletion of PKD1 (and CaMKII␦ knock-out) limit cardiac remodeling after aortic constriction (5,22) and novel PKD inhibitors have had some success in the prevention of pathological hypertrophy (23)(24)(25) as well as of pancreatic and prostatic cancer growth (17,26). In the heart, a better mechanistic understanding of how cardiomyocyte PKD and CaMK are activated in response to pathogenic neurohumoral stimuli (5-6) is needed to evaluate the therapeutic potential of specific PKD/ CaMKII inhibition.…”
mentioning
confidence: 99%